Manajemen komunikasi pembinaan pelestarian plasma nutfah Sapi Rambon di Banyuwangi - Eko Nugroho; Siti Azizah (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
There are a lot of research results related to cattle productivity improvements have been conducted by many researchers, scientist and academicians. However, these results are not well disseminated to the society due to lack of appropriate dissemination method. Therefore, this research tended to develop communication strategy of Rambon cattle conservation which was suitable with farmer’s need. Seventy five farmers in Glagah sub-district were selected purposively as respondents. Observation as well as interview using questionnaire were done to obtain the primary data. These data then were analyzed using SPSS. The results showed that respondents were dominated by men with 53.55±13.12 years of age. Most of them were less educated and worked as farmers or farm labours. They earned varied average income from IDR 100,000 to IDR 3,000,000 depending on the type of occupation. The number of family labour per household was 2.44±0.96 people. In relation to the design of communication strategy which was suitable with farmer’s needs, the results found that farmers tended to get extension about Rambon cattle farming practices. Evening was the most appropriate time to conduct the extension and took place in the local administrative office. The preferable extension agent should be male who had expertise in Rambon cattle faming practice, nice, friendly, capable and had ability to speak in Bahasa as well as local language. The preferable extension message should contain guideline how to keep Rambon cattle and should be delivered shortly, fun and had a lot of humours. The respondents were more likely to select face to face media as personal media supported by local television as mass media.   Keywords: extension, Rambon cattle